Viabilidade econômica da produção do ASAC para uso no concreto asfáltico - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
It is known that the Amazon region lacks superficial raw material to obtain stony aggregates used in civil construction, more precisely in paving. Many studies have been carried out in order to identify an alternative material that can replace the use of rolled pebble and gravel in the production of asphalt concrete due to the high cost of these raw materials due to the transport distance of the superficial rock deposits (gravel), as well as the worrying environmental impact resulting from the extraction of the rolled pebble from river beds, combined with its equally high cost with transportation. Among so many alternative materials studied, the calcined clay synthesized aggregate (ASAC) stands out, replacing these coarse aggregates, since the clay presents a large reserve in the State of Amazonas.The viability of this material has already had its technical and environmental proof. What we propose in this study is the proof of the economic viability of ASAC in substitution for the rolled pebble in the production of Hot Machined Bituminous Concrete (CBUQ) in the paving of highways in our region, especially in places far from Manaus.
Keywords: Argila - Análise; Brita; Agregados (Materiais de construção); Concreto asfáltico; Concreto Betuminoso Usinado a Quente; ENGENHARIAS; Agregado sinterizado de argila calcinada; Argila; Agregado graúdo